The Employment of the Savior Concept in Literature: Iraqi Novelistic production post-war of 2003 - Jubair, Ahmed Karyosh; Abu, Dr. Abdul Ghani bin (International Journal of English Literature and Social Sciences (IJELS), 2019)
This article focuses on studying the savior as a concept from both sides linguistically and as an idea or philosophy. The study has tackled many beliefs and conventions reflected in different societies. The focus was on using such concept in the contemporary Iraqi novels and how the novelists employed it in conveying the concerns, hopes and aspirations of the ordinary man in the local areas of Baghdad under the invasion of the U.S. troops. The writers tend to use fantasy style to decrease or mitigate the cruelty of the period of invasion where the scene was full of death, bloodshed atmosphere. The sample of this study is Frankenstein in Baghdad, the novel was written by Ahmed Saadawi, one of the most famous Iraqi novelists who gained global reputation. The novel represents the postcolonial literature in Iraqi contemporary novelistic production. This novel was short listed for the coveted International Prize for Arabic Fiction in 2014 and won the prize. In 2018, Frankenstein in Baghdad was shortlisted for the Man Booker International Prize after it has been translated by Jonathan Wright into English. It was also translated into more than 30 different languages.A textual analysis of this novel is presented to explore the new style and discourse language. The study concluded that the themes and discourses are changed and witnessed new trends and style and became as a real reflection of the life and its restless details of the Iraqis. The novelists for the first time were able to touch the three forbidden subjects; sex, religion and politics. The noticeable concept used in the new Iraqi novel is the use of the Savior concept as a theme adopted from the universal phenomena Frankenstein of Mary Shelley. This concept is employed consciously to convey the idea of the Savior as the last resort and hope for those who are suffering from marginalization and live in impoverished areas in neighborhoods of Baghdad. The aim of this article is to shed light on the use of the savior concept fantastically in literature especially in the novel genre in Iraq after the war of 2003 and U.S invasion. It gives a background and some definitions and usages of this concept in literature in certain civilizations and religions.